Pathogenic Assay of Probiotic Bacteria Producing Proteolytic Enzymes as Bioremediation Bacteria Against Vannamei Shrimp Larvae (Litopenaeus vannamei) - Wilis Ari Setyati; Muhammad Zainuddin; Person Pesona Renta (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2017)
Application of bacteria in bioremediation of shrimp culture ponds is one of the methods used to clean internal pollutants. This study aimed to evaluate the pathogenicity of extracellular proteolytic enzyme produced by the probiotic bacteria as bioremediation bacteria on vannamei shrimp larvae culture. There were five probiotic bacteria, which were successfully isolated from the sediments served as substrate in mangrove area. The isolated bacteria were coded in number as 13, 19, 30, 33, and 36. Pathogenic bacteria Vibrio harveyi was used as positive control. Pathogenic assay was carried out in two different bacterial concentrations, i.e. 10⁸ and 10⁶ cells.mL-1. The results showed that the lowest survival rate (SR) of shrimp larvae in positive control V. harveyi was 53 and 65%. Whereas isolates with the highest SR value (100%) were obtained from bacteria coded as 13 and 30. Isolates no. 19, 33 and 36 had SR of more than 90%. Total plate count (TPC) data showed that the bacteria increased significantly at the end of the study with an average increase value of 24%. The smallest TPC value was shown by bacterial isolate no. 19, while the largest was obtained from the isolate no. 13. These results suggest that all probiotic bacteria were not pathogenic to the vannamei shrimp larvae. Keywords: aquaculture, shrimp, bioremediation, pathogenesis, vibrio.